2008
DOI: 10.1021/ja808110d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure Revision of Nakiterpiosin

Abstract: This manuscript describes a convergent synthesis and the revision of the relative stereochemistry of nakiterpiosin, a marine C-nor-D-homosteroid. Our synthesis features a late-stage carbonylative Stille cross-coupling reaction and a photo-Nazarov cyclization reaction that deliver the complete nakiterpiosin skeleton efficiently. Nakiterpiosin (1) is a marine sponge metabolite that exhibits potent cytotoxicity against the P388 murine leukemia cell line (GI 50 10 ng/mL) ( Figure 1). 1 It was the first C-nor-Dhomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(62 citation statements)
references
References 67 publications
(37 reference statements)
1
60
0
1
Order By: Relevance
“…We recently proposed to revise their relative configuration to that shown in 1 and 2 by analyzing the spectroscopic data of their fragments. We further synthesized 1 and 3 and confirmed that the structure of nakiterpiosin should be 1 3. We present herein the details of our synthetic studies and spectroscopic analysis of nakiterpiosin ( 1 ) and 6,20,25- epi -nakiterpiosin ( 3 ).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…We recently proposed to revise their relative configuration to that shown in 1 and 2 by analyzing the spectroscopic data of their fragments. We further synthesized 1 and 3 and confirmed that the structure of nakiterpiosin should be 1 3. We present herein the details of our synthetic studies and spectroscopic analysis of nakiterpiosin ( 1 ) and 6,20,25- epi -nakiterpiosin ( 3 ).…”
Section: Introductionmentioning
confidence: 68%
“…Our first-generation approach3 is outlined in Figure 5. We opted to construct the central cyclopentanone ring at a late-stage for convergency reasons.…”
Section: Synthetic Plansmentioning
confidence: 99%
“…The highly diastereoselective character of the vinylogous aldolization, strongly favoring 23,24-syn-24,25-anti-configured isomer 262, may be rationalized based on a Diels-Alder-like transition state (cf. During the total synthesis of nakiterpiosin (271) and nakiterpiosinone (272), two related C-nor-D-homosteroids, an accurate screening of 14 different Lewis acid promoters, emerged Sn(OTf) 2 as the best performer in terms of both conversion and stereoselectivity (Scheme 2.69) [114,115]. Thus, the tin(II) triflate-catalyzed VMAR between aldehyde 269 (90% ee) and 3-methyl-2-(triisopropylsiloxy)furan (3-Me-TIPSOF) (268) yielded 270 with 83% conversion, as the only diastereomer in 80% isolated yield and 90% ee.…”
Section: Furan-derived Silyloxy Dienes -Diastereoselective Processesmentioning
confidence: 99%
“…In the latter case the reaction was performed in the presence of H 2 O (Scheme 10). 213,214 Water has also been used in other total syntheses using DMP in CH 2 Cl 2 , 97,121,122,215 because it accelerates the reaction. 13…”
Section: 211mentioning
confidence: 99%